The effect of emotional intelligence on behavioral satisfaction: the mediating effect of recycle behavior - Mehpare Tokay ARGAN; Metin ARGAN; Mehmet Tahir DURSUN (Present Environment and Sustainable Development, 2022)
Environmental behavior and recycle behavior both are related to having emotional intelligence by the way of thinking environment. Recent studies about the environment and recycle behavior paid attention to human’s individual sensitiveness as environmental value, west management, or environmental protection. However, the influences of emotional intelligence on behavioral satisfaction were left out. To fill this gap, the current study investigates the association emotional intelligence on behavioral satisfaction among university students, and recycle behavior mediates this association. The model is empirically tested with data collected from 477 participants of university students by questionnaire. Dataset adopts the method of structural equation modeling to explore the mediating role of recycle behavior between emotional intelligence and behavioral satisfaction. Results indicate that participants’ emotional intelligence toward environmental behaviors positively affects their behavior satisfaction, and in this result, recycle behavior has mediating affect between emotional intelligence and behavior satisfaction.